Student Enrolment Prediction Model in Higher Education Institution: A Data Mining Approach - Ab Ghani N.L.; Che Cob Z.; Mohd Drus S.; Sulaiman H. (Springer Verlag, 2023)
Data Analytics; Decision trees; Education computing; Forecasting; Regression analysis; Students; Trees (mathematics); 10-fold cross-validation; Decision tree modeling; Educational data mining; Higher education institutions; Higher learning institutions; Logistic regressions; Predictive models; Student enrolment; Data mining